Correlaciones canónicas entre variables de habilidad y variables de lectura - Fogliatto, Hermelinda M. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The relationship obtaining between general ability and reading variables was studied. The Test of General Ability and Test of Reading, Form CE, level 5 of the Interamerican Series were administered to two groups of students, one from psychology and one from education. Canonical correlations were calculated between the three parts of the Test of General Ability (independent variables) and the three parts of the Test of Reading (dependent variables). For the two groups studied, only the first canonical correlation was significantly different from zero. For the psychology students, the canonical vector associated with the Test of General Ability reflected verbal ability, and the canonical vector associated with the Test of Reading reflected abstraction and, to a degree, expression. For the students in education, the canonical vector associated with the predictor variables reflected numerical ability, and the canonical vector associated with the criterion variables reflected expression and comprehension.